Tinjauan Analisis Manfaat dan Dampak Sinar UV-C dalam Bidang Pangan dan Pertanian - Naufal Cahyo Widodo; Akmal Aziz; Zada Aulia Munawaroh; Hafiz Anzhari; Diyajeng Luluk Karlina (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
UV-C light exposure has been widely applied in food and agriculture to improve product quality, safety, and durability. UV-C light has short wavelengths that are effective in inactivating pathogenic microorganisms in food and plant products, thereby reducing the risk of contamination and extending product shelf life. In agriculture, the application of UV-C light to crops can increase crop resistance to pests and diseases, and stimulate certain physiological responses that support growth.